Mechanical behavior of additively manufactured nanoclay/HDPE nanocomposites - Beesetty, Pavan; kale, Aditya; Patil, Balu; Doddamani, Mrityunjay (Composite structures, 2020)
•NC/HDPE nanocomposites are successfully printed without any warpage.•H5 filament registered the highest modulus.•The tensile strength of H5 is highest among all the composition, which is ~35% higher compared to neat HDPE filament.•3D printed H, H0.5, H1, H2 and H5 modulus is 1.66, 1.34, 1.34, 1.33, and 1.28 times higher than their respective filament.•H5 print exhibited the highest UTS and is 22% higher as compared to H.•Highest flexural modulus and strength are exhibited by H5, which is 1.12 times respective values of HDPE print. Nanoclay (NC) has blended with relatively inexpensive, widely consumed HDPE (high density polyethylene) for the development of filament to be used in 3D printers. NC/HDPE blends are prepared by varying NC wt. % (0.5, 1, 2, and 5) and are subjected to melt flow index (MFI) measurements. MFI has noted to be decreasing with NC loadings. NC/HDPE nanocomposite blends are further extruded using a single screw extruder. Developed nanocomposites filaments are fed to the fused filament fabrication (FFF) based 3D printer for realizing NC/HDPE nanocomposite prints. The density of printed sample increases with filler content. Filament and printed samples thermal study is carried out using differential scanning calorimeter (DSC). NC addition increases crystallinity and crystallization temperature without significant change in melting peak temperature. Freeze fractured prints reveal the uniform distribution of NC in HDPE. The tensile test is conducted on the filaments and prints. Further printed nanocomposites are subjected to flexural investigations. Tensile modulus and strength of filament increase with NC additions in HDPE matrix. Tensile and flexural properties (modulus and strength) of the nanocomposite prints increases with NC content. Finally, results obtained from the tensile and flexural tests of prints are compared with different HDPE composites available in the literature.